Adenine-functionalized conjugated polymer as an efficient photocatalyst for hydrogen evolution from water. (12th August 2022) - Li, Renlong; Zhang, Xiongbo; Zhang, Chong; Lu, Jianfeng; Wang, Ji-Chao; Cui, Cheng-Xing; Yang, Xiye; Huang, Fei; Jiang, Jia-Xing; Zhang, Yuping
Abstract: Conjugated polymers have emerged as a promising class of organic photocatalysts for photocatalytic hydrogen evolution from water splitting due to their adjustable chemical structures and electronic properties. However, developing highly efficient organic polymer photocatalysts with high photocatalytic activity for hydrogen evolution remains a significant challenge. Herein, we present an efficient approach to enhance the photocatalytic performance of linear conjugated polymers by modifying the surface chemistry via introducing a hydrophilic adenine group into the side chain. The adenine unit with five nitrogen atoms could enhance the interaction between the surface of polymer photocatalyst and water molecules through the formation of hydrogen bonding, which improves the hydrophilicity and dispersity of the resulting polymer photocatalyst in the photocatalytic reaction solution. In addition, the strong electron-donating ability of adenine group with plentiful nitrogen atoms could promote the separation of light-induced electrons and holes. As a result, the adenine-functionalized conjugated polymer PF6A-DBTO2 shows a high photocatalytic activity with a hydrogen evolution rate (HER) of 25.21 mmol g −1 h −1 under UV-Vis light irradiation, which is much higher than that of its counterpart polymer PF6-DBTO2 without the adenine group (6.53 mmol g −1 h −1 ). More importantly, PF6A-DBTO2 without addition of a Pt co-catalyst also exhibits an impressive HER of 21.93 mmol g −1 h −1 under visible light (λ > 420 nm). This work highlights that it is an efficient strategy to improve the photocatalytic activity of conjugated polymer photocatalysts by the modification of surface chemistry. Graphical abstract: An adenine-functionalized conjugated polymer PF6A-DBTO2 was constructed and developed as an efficient photocatalyst for hydrogen evolution from water. A hydrogen evolution rate (HER) of 25.21 mmol g −1 h −1 was obtained for PF6A-DBTO2 without addition of a Pt co-catalyst, which is much higher than that of its counterpart polymer PF6-DBTO2 with alkyl side chains. Image 1 Highlights: An adenine-functionalized conjugated polymer was developed for highly efficient photocatalytic hydrogen evolution. The enhanced contact between adenine groups and water enables more efficient charge transfer and separation. The adenine-containing polymer photocatalyst exhibited a much higher HER than the counterpart polymer with alkyl chains.